Legal And Institutional Challenges In Railway Waste Management: A Comparative Analysis Of India’s Regulatory Framework With International Standards (Journal of Namibian Studies : History Politics Culture, 2023)
Railway waste management in India presents a complex challenge, given the vast scale of railway operations and the diverse waste streams generated, including solid, hazardous, and biomedical waste. While legal frameworks such as the Railways Act, 1989, Solid Waste Management Rules, 2016, and Hazardous Waste Management Rules, 2016 establish guidelines for waste disposal, enforcement gaps and infrastructural deficiencies hinder their effective implementation. Furthermore, railway hospitals are subject to the Bio-Medical Waste Management Rules, 2016, yet compliance remains inconsistent. The recently enacted Bharatiya Nagarik Suraksha Sanhita (BNSS), 2023, may introduce new provisions relevant to railway waste management, but its practical impact remains unclear.This paper critically examines the existing legal and policy framework, identifies implementation challenges, and assesses international best practices from the European Union, United Kingdom, and Japan. Drawing comparisons with these models, the paper argues that India’s railway waste management system requires stronger regulatory enforcement, technological interventions, and coordinated governance among Indian Railways, municipal authorities, and regulatory bodies. The study further proposes policy recommendations to enhance sustainability, compliance, and accountability. By addressing these deficiencies, Indian Railways can align itself with global best practices, contributing to a more efficient and environmentally responsible waste management system.